Analisis Transformasi Komunikasi RRI Padang dalam Konteks Era Digital: Tantangan dan Peluang - Nurliansyah, Vira; Rezika, Mutiara; Syafril, Rizki (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2024)
This research aims to examine and analyze Communication Transformation in the Digital Era conducted by RRI PADANG. The study employs a qualitative method with a descriptive approach. Data collection is carried out through interviews, structured observation, documentation, and literature review. The results of this research indicate that RRI PADANG has undergone transformation in delivering and receiving information. One form of transformation undertaken is the introduction of the RRI Digital Application, where this application can be accessed for free by the public in real-time. Within the application, features are provided for the public to enjoy such as listening to radio, reading news, listening to music, and podcasts. Additionally, users can also write articles related to current news which can be viewed by the public.